Dampak Kerusakan Sumber Daya Alam Akibat Kegiatan Penambangan Komoditas Batu Gamping di Kecamatan Panceng, Kabupaten Gresik, Provinsi Jawa Timur - Ivan Ardiansyah; Naufal Syarif Ardyanto; Tuhu Agung Rachmanto (International Forum of Researchers and Lecturers, 2024)
The aim of limestone mining activities is to obtain the main raw material, namely limestone, which can then be used as a construction raw material such as cement. This data collection method is to collect primary data obtained from identifying activity locations and secondary data obtained from Journal Reviews and other scientific articles and then compiling them into a narrative. From the results of this analysis, it can be seen that there is a positive impact, namely the recruitment of workers from the local area and a negative impact, namely a decrease in ambient air quality, a decrease in water quality, soil erosion, disruption of flora and fauna and plant vegetation.